MENAKAR POTENSI PENGEMBANGAN DESA WISATA RELIGI DALAM MENDUKUNG PEMULIHAN EKONOMI DI PROVINSI GORONTALO - Sri Apriyanti Husain (Sekolah Tinggi Pariwisata Sahid Surakarta, 2023)
Covid 19 has had an effect on all human life, including the tourism sector. On the other hand, the tourism sector is considered to be one of the superior sectors and is expected to contribute to the Economic Recovery. The purpose of writing this paper is to measure the potential for the development of a Religious Tourism Village in supporting the Economic Recovery in Gorontalo Province. In preparing this paper the author uses a descriptive method with a qualitative approach. This approach is considered appropriate by the author, because with a qualitative approach, the author can explore more about the potential for developing a Religious Tourism Village in supporting Economic Recovery in Gorontalo Province. The results of this study indicate that Gorontalo Province has potential in developing Religious Tourism Villages. Religious Tourism Villages that can be developed to support national economic recovery are Bongo Village which is located in Batudaa Pantai District, Gorontalo Regency and Tri Rukun Village which is in Wonosari District, Boalemo Regency.